2022
DOI: 10.1155/2022/8555417
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Fluticasone and Salmeterol Dry Powder in Treating Patients with Bronchial Asthma and Its Effect on Inflammatory Factors and Pulmonary Function

Abstract: Objective. To evaluate the efficacy of fluticasone and salmeterol dry powder in treating patients with bronchial asthma and its effects on inflammatory factors and pulmonary function. Methods. One hundred patients with bronchial asthma, admitted to our hospital between April 2019 and June 2020, were enrolled and assigned into two groups using the random number table method. The observation group (n = 50) received budesonide powder, and the experimental group received fluticasone and salmeterol dry powder. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Substitution of the 1,3,5trifluorobenzene moiety in place of a nonfluorinated benzene ring produces a four-fold Fluticasone 4 is used for relieving nasal symptoms such as sneezing, itching, and runny nose provoked by allergies; recent studies use this compound in combination with other medications to improve its effects against allergic rhinitis [38][39][40]. Also, fluticasone is combined with salmeterol and prescribed under the medication named Advair for the treatment of asthma as well as other obstructive airway diseases [41,42]. Fluticasone 4 containing the electron-withdrawing fluorine atom demonstrated greater topical activity compared to other analogs and increased glucocorticoid and mineralocorticoid effects [43].…”
Section: Examples Of Pharmaceuticals Containing Fluorinementioning
confidence: 99%
“…Substitution of the 1,3,5trifluorobenzene moiety in place of a nonfluorinated benzene ring produces a four-fold Fluticasone 4 is used for relieving nasal symptoms such as sneezing, itching, and runny nose provoked by allergies; recent studies use this compound in combination with other medications to improve its effects against allergic rhinitis [38][39][40]. Also, fluticasone is combined with salmeterol and prescribed under the medication named Advair for the treatment of asthma as well as other obstructive airway diseases [41,42]. Fluticasone 4 containing the electron-withdrawing fluorine atom demonstrated greater topical activity compared to other analogs and increased glucocorticoid and mineralocorticoid effects [43].…”
Section: Examples Of Pharmaceuticals Containing Fluorinementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%